Adapting postmodernist art curricula in Malaysia and Indonesia - Iwan Zahar (2012)
Postmodernist arts movement influence over Malaysia and Indonesia artists for over twenty years, and many Malaysian and Indonesian artists utilize these concept. However, the art education in some universities in Indonesia and UMK are still based on modernist curriculums. Adapting postmordenist curricula will be challenged in Malaysia and Indonesia because the social issues and different principal are required to be integrated into the curricula. Students should learn interdisciplinary subject matter; various media and technologies; local content (non western) and western concepts of space and design; hidden-stream art and artist; and enlarge artistic canon. Postmodernist curricula enrich existing modernist curricula. In order to know the student’s prior knowlege about postmodernist issues, survey method are employed to investigate 50 students in Universitas Tarumanagara Jakarta in 2010, and 18 students in Universiti Malaysia Kelantan in 2011. The results show students from both universities have a little knowledge about postmodernist issues. Moreover, the survey used photo and film criticism instruments to know the student’s prior knowledge. I recommend to develop postmodernist curricula: (1) integration value and principals of indigenous artist; (2) integration postmodernism (art history) and art criticism in curricula; (3) develop problem-based learning for art theory and project-based learning for studio productions; (4) integrate contemporaries social issues such as feminism, global warming, war, peace, violence, multiculturism, proverty to the course with various teaching methods.